Realism and Reality : Studies in the German Novelle of Poetic Realism - Silz, Walter (Chapel Hill The University of North Carolina Press, 1954)
In this 1954 study of poetic realism and the "Novelle" form, Silz examines nine "Novellen" by Brentano, Arnim, Droste-Hülshoff, Stifter, Grillsparzer, Keller, Meyer, Storm and Hauptmann. Through his textual interpretation of each of these works Silz draws the threads of the transition from Romanticism to Naturalism as well as the development of the "Novelle" form.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; German Studies; Literature